Design of perching flights via a motion capturing platform - Chao, Deng (2015)
Unmanned Arial Vehicles (UAVs) are aircrafts without pilot physically present onboard. In the past few years, there have been extensive activities in developing UAVs, especially in military and civil areas. Since UAV has no pilot onboard, it is important to plan the UAV flight trajectory beforehand. There are many trajectory planning strategies for UAV. Tau theory is one of it. Tau theory has been first proposed by David Lee and analysed in several papers. It is a bio-inspired flight trajectory planning method that was established from the natural motion of perching animals such as birds and therefore being utilized on UAVs perchings. The main idea of tau theory is that, the tau-dot is to be kept constant between 0 and 0.5 in order to achieve a smooth perching with zero velocity and acceleration. This entire project is done by two people, I am in charge of the design and development of the flight trajectory of UAV mainly through the use of tau theory, and my colleague is working on developing the object tracking system through camera mounted beneath the UAV. This report presents the design and development of flight trajectory that applied tau theory as the UAV guidance for perching trajectory. Algorithms that allow the calculation of flight trajectories for UAV were presented. Before the perching trajectory is developed, this project assisted my colleague in flight trajectory planning and designing for his object identification and tracking project. Then, perching trajectory of parrots was developed for simulation. After which, strategies for perching trajectory using tau theory with constant tau-dot was applied for the x direction, x and y directions, and coupling x and y directions. And then positive conclusions were drawn from the experimental results.